Exercise Testing and Prescription in Patients with Congenital Heart Disease - A. D. J. ten Harkel; T. Takken (International Journal of Pediatrics)
The present paper provides a review of the literature regarding exercise testing, exercise capacity, and the role of exercise training in patients with congenital heart disease (CHD). Different measures of exercise capacity are discussed, including both simple and more advanced exercise parameters. Different groups of patients, including shunt lesions, pulmonary valvar stenosis, patients after completion of Fontan circulation, and patients with pulmonary arterial hypertension are discussed separately in more detail. It has been underscored that an active lifestyle, taking exercise limitations and potential risks of exercise into account is of utmost importance. Increased exercise capacity in these patients is furthermore correlated with an improvement of objective and subjective quality of life.